Artificial Intelligence in the Era of Society 5.0: Compromising Technological Innovation Through theWasathiyyah Approach within the Framework of Islamic Law - Kosasih, Engkos; Islamy, Mohammad Rindu Fajar; Wiwaha, Rizzaldy Satria (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This research aims to investigate the legality of using ChatGPT in education from the perspective of the Muslim community, focusing on ethics, Islamic law, and Islamic values. Since the emergence of Artificial Intelligence (AI) in the early 2020s, public debates on AI have generated both support and criticism. Western scholars such as Kelly Ann Allen, Joseph A. Crawford, and Ricky Acanto argue that AI significantly contributes to enhancing learning, personalizing instruction, and managing resources. However, concerns have arisen regarding the negative impacts of AI, such as cheating and plagiarism. Islam, as a timelessly relevant religion, offers wise solutions to these issues. This empirical study employs a literature review approach using the Systematic Quantitative Literature Review method to map the dynamics of the AI ChatGPT discussion among scholars. This study adheres to Miles and Huberman’s three stages of data analysis: data display, reduction, and conclusion. The research findings indicate that internalizing the values of Wasathiyyah is crucial for developing a broad perspective on societal acceptance of AI ChatGPTs. Religious moderation emphasizes that Islam does not reject AI, but rather emphasizes the importance of mitigating its negative effects. With proportional policies, AI is expected to collaborate with humans to accelerate civilization forward.